Triggers leading to substance abuse in patients admitted at de-addiction centers in a city of North Karnataka: A qualitative study - Anas Mailadi; Rajesh R. Kulkarni (Al Ameen Medical College, 2023)
Background: Substance abuse is defined as ''Harmful or hazardous use of psychoactive substances, including alcohol and illicit drugs''. Main substances abused include tobacco, alcohol, cocaine, opiates, hallucinogens, amphetamines, prescription and over-the-counter drug abuse. Substance abuse results in health and social issues for those who consume them, and also to the family members and the community. The present study aims to find out the triggers leading to substance abuse in patients admitted at de-addiction centers in Belagavi, a city of North Karnataka. Objective: To find out different triggers leading to substance abuse by qualitative in depth interview. Methodology: It was a Qualitative study done using in depth interview from 1st January 2021 to 30th April among 25 participants admitted at the five de-addiction centres located at Belagavi city during the study period. Results: When participants were asked about what was there trigger which lead to initiation of substance use, we got 4 major themes, peer pressure, family background for addiction, relationship breakdown/academic failures, physical environment. Conclusion: There is a need for further studies to detect the community prevalence of substance abuse and the reasons for initiation. Community based studies are vital to find out the magnitude of the problem and its related factors for better decision making.